Provision of Compensation and Damages for Termination of a Fixed-Term Employment Agreement Before the End of the Term with Legal Certainty - Dedy Surya Mulyono; Abdul Rachmad Budiono; Budi Santoso (PATTIMURA Legal Journal, 2025)
Introduction: Fixed-Time Employment Agreement before the end of the period often creates legal uncertainty regarding the provision of compensation and damages. The lack of clarity in regulations encourages the need for legal analysis and reconstruction to ensure certainty, justice, and protection of rights for workers and employers. Purposes of the Research: This research aims to explore and reinterpret the concepts of damages and compensation within the framework of employment law, particularly in the context of early termination of Fixed-Term Employment Agreements. By examining the legal ambiguities that often arise in such cases, the study seeks to develop a reconstructed legal model that ensures clarity and consistency in determining entitlements. This reconstruction is expected to contribute to the realization of equitable treatment and stronger legal safeguards for both employers and employees involved. Methods of the Research: This study uses a legal research method with a statutory approach and a case approach. The legal materials used include primary legal materials (statutory regulations and court decisions), secondary (books, research results and journals) and tertiary (Indonesian dictionary). The legal materials are obtained from studies which will then be analyzed using analysis techniques in the form of systematic interpretation and grammatical interpretation. Results Main Findings of the Research: The results of the analysis show that the meaning of compensation and damages in Fixed-Time Employment Agreement have fundamental differences, where compensation is given due to termination of employment that is not in accordance with the provisions, while compensation is a reward for work that has been completed. Legal certainty related to both terms is important to ensure justice and the implementation of workers' rights consistently.